A Cross-Sectional Study of the Distribution Patterns and Potential Determinants in Plasma Selenium Status Among Chinese Adults With Hypertension - Wang, Zhuo; Lin, Tengfei; Wei, Yaping; Song, Yun; Liu, Lishun; Zhou, Ziyi; Huang, Xiao; Chen, Ping; Liu, Chengzhang; Li, Youbao; Wang, Binyan; Li, Jianping; et al. (Frontiers in Nutrition, 2022)
Selenium (Se) is an essential trace element in selenoproteins biosynthesis for the human body and plays an important role in the prevention and control of subsequent cardiovascular disease (CVD) in adults with hypertension However, reports on Se status and its potential determinants in populations from different regions of China are limited, especially data on adults with hypertension, a high-risk group more vulnerable to oxidative stress. Thus, we conducted a cross-sectional study from February 2017 to May 2018 of 2599 participants (1389 males and 1210 females) on middle-aged to elderly adults with hypertension with a mean age of 63.1 (SD, 13.3) years from 14 provinces of China, and aimed to examine the relationship of plasma Se status with demographic characteristics and lifestyles. Overall, male participants (mean value, 75.0 μg/L) tended to have higher plasma Se concentrations than females (73.7 μg/L) when controlling for relevant factors. There were significant differences among regions, and in age and body mass index (BMI) in plasma Se distribution, and plasma Se concentrations were significantly lower among those in regions with relatively lower Se, aged 60 years or older and with BMI lower than 28 kg/m2. Moreover, a higher frequency of meat consumption (1-2 or ≥3 times/week vs. <1 time/week) was significantly associated with higher plasma Se concentrations in males and females, and male alcohol drinkers had significantly higher plasma Se concentrations than non-alcohol drinkers. Adequate consumption of fruits and vegetables (0.5-1.5 kg/week) was associated with higher plasma Se concentrations among females, but was associated with relatively lower plasma Se concentrations in males. Our results indicated relatively low plasma Se status in Chinese adults with hypertension from 14 provinces, while, specific factors including geographic, demographic and lifestyle characteristics and blood pressure were significantly associated with plasma Se status in this hypertensive population. In addition, more studies are required to further evaluate dietary structure and other lifestyle factors that inﬂuence circulating Se status.